• Упростите выражение
    Помогите срочно
    (a^-3)^-2*a^-8/a^-3

Ответы 1

  •  \frac{( a^{-3} ) ^{-2} * a^{-8} }{ a^{-3} } = \frac{ a^{(-3)*(-2)}* a^{-8}  }{ a^{-3} } = \frac{ a^{6} * a^{-8} }{ a^{-3} }= \frac{a ^{6-8} }{ a^{-3} }= \frac{ a^{-2} }{ a^{-3} }= a^{-2-(-3)}= a ^{-2+3}     =a
    • Автор:

      aidynptaq
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years